Multiomics Analysis of Exportin Family Reveals XPO1 as a Novel Target for Clear Cell Renal Cell Carcinoma - Yanhong Hao; Hongchun Lv; Xu Yan; Yanyan Liang; Aimin Jiang; Yuxia Zhao (International Journal of Genomics)
Conclusion: This study analyzed the variations of exportin gene family members at the pan-cancer level and identified two distinct ccRCC subtypes, which can guide personalized management of patients.